Topical rapamycin versus betamethasone dipropionate ointment for treating oral erosive lichen planus: a randomized, double‐blind, controlled study. (7th April 2020) - Samimi, M.; Le Gouge, A.; Boralevi, F.; Passeron, T.; Pascal, F.; Bernard, P.; Agbo‐Godeau, S; Leducq, S.; Fricain, JC; Vaillant, L.; Francès, C.
Abstract: Background: Although superpotent topical corticosteroids are the first‐line treatment for oral erosive lichen planus (OELP), topical rapamycin was found efficient in a previous case series. Objectives: To compare the efficacy and safety of topical rapamycin and betamethasone dipropionate ointment for OELP in a randomized, double‐blind trial. Methods: Patients were randomized to receive treatment with betamethasone dipropionate ointment 0.05% in Orabase ® or topical rapamycin solution (1 mg/mL) on lesions twice daily for 3 months, followed by 3 months of observation. The primary outcome was clinical remission after 3 months of treatment. Secondary outcomes were clinical remission after 1 and 2 months, reduced oral pain and reduced impact on food intake after 3 months, clinical recurrence after treatment withdrawal, and adverse events. Results: During a 4‐year period, 76 patients were randomized and 75 received treatment (rapamycin, n  = 39; betamethasone, n  = 36). At 3 months, 39.4% of patients with betamethasone and 27.3% with rapamycin showed clinical remission (odds ratio 0.68, 95% CI [0.24; 1.89]; P  = 0.46). Rates of remission after 1 and 2 months, reduction in pain and impact on food intake after 3 months, were higher with betamethasone than rapamycin. Recurrence of oral erosions was similar between groups. Adverse events occurred in 43.6% of patients with rapamycin (mostly burning sensation, impaired taste) and 27.8% with betamethasone (mostly oral candidiasis). Conclusion: Although the study was limited by insufficient recruitment, we did not find any superiority of topical rapamycin over betamethasone dipropionate ointment for OELP. Given the rapid remission and pain improvement in the betamethasone group, it appears that superpotent topical corticosteroids should remain the first‐line treatment for OELP.